Influence of boron nitride on morphological, mechanical, thermal and wear characteristics of epoxy nanocomposites. (28th July 2020) - Navaneethakrishnan, G.; Karthikeyan, T.; Saravanan, S.; Selvam, V.
ABSTRACT: The nanocomposites materials are extensively used in the field of automotive and electronic industries for its superior properties. Boron nitride (BN)/epoxy nanocomposites containing different percentages of BN particles are prepared by liquid casting process. The mechanical properties such as hardness, tensile, flexural and impact strength of the composites were analyzed. The even distribution of the BN particles in the epoxy matrix was confirmed by scanning electron microscopy. Due to the promising properties of BN such as lower shear, higher lubrication and load-bearing characterstics, it was used as reinforcement in the polymer matrix composites to meet the purpose of lower wear rate and coefficient of friction.